TWO PORT COMPACT MIMO ANTENNA FOR ISM BAND APPLICATIONS - Sharma, Kanhaiya; Pandey, Ganga Prasad (Progress in electromagnetics research C Pier C, 2020)
This article presents a compact size and high isolation 2 x 2, Multi-Input Multi-Output (MIMO) antenna for Industrial Scientific and Medical (ISM) band and 5G lower frequency band of 5G applications. Mutual coupling has been a great challenge in these applications. To improve isolation between elements of 2 x 2 MIMO antennas, a mushroom-shaped electromagnetic bandgap (EBG) and a fractal shaped EBG have been investigated. The overall size of the proposed antenna is 38.2 x 95.94 x 1.6 [mm.sup.3] with inter-element spacing (edge to edge) of 0.140[lambda]. The proposed antenna has been designed, simulated, fabricated, and tested. The resulting outcome shows that the antenna operates in the band of 2.43-2.50 GHz and radiates in [TM.sub.10] mode. By using fractal shaped EBG, isolation of -24.67 dB is achieved. Apart from isolation, other performance parameters of the MIMO antenna are verified. The proposed antenna is suitable for weather radar, surface ship radar, satellite communication, and wireless local area network (WLAN) applications.